Peran Volunteer Dalam Penyelenggaraan MICE (Studi Kasus : Sriwijaya Expo 2022 oleh PT. Garindo Media Utama) - Handika Fikri Pratama; Muhammad Iqbal; Melsa Agustina (Jurnal Terapan Ilmu Ekonomi, Manajemen dan Bisnis, 2024)
This research aims to determine the role of volunteers in organizing the MICE study in the Sriwijaya Expo case. In organizing events, it is often known that non-professional staff are used whose expertise is not yet available. The approach used is qualitative with triangulation of source, technical and time data processing techniques. There were two sources, namely the deputy director of PT Garindo Media Tama and Sriwijaya Expo 2022 volunteers. The results of this approach found that during the establishment process there was no discipline and low initiative. However, even though there is a shortage, the organizers feel helped by the presence of volunteers and will continue to use volunteers in future activities.